2021
DOI: 10.7546/nntdm.2021.27.4.15-24
|View full text |Cite
|
Sign up to set email alerts
|

On Robin’s criterion for the Riemann Hypothesis

Abstract: Robin’s criterion says that the Riemann Hypothesis is equivalent to \[\forall n\geq 5041, \ \ \frac{\sigma(n)}{n}\leq e^{\gamma}\log_2 n,\] where \sigma(n) is the sum of the divisors of n, \gamma represents the Euler–Mascheroni constant, and \log_i denotes the i-fold iterated logarithm. In this note we get the following better effective estimates: \begin{equation*} \forall n\geq3, \ \frac{\sigma(n)}{n}\leq e^{\gamma}\log_2 n+\frac{0.3741}{\log_2^2n}. \end{equation*} The idea employed will lead us to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For instance, the present author [7,Theorem 1.3] proved that the inequality σ(n) n < e γ log 2 n + 0.0094243e γ log 2 2 n holds unconditionally for every integer n > 5040. The initial motivation to write this paper is based on a recent paper by Aoudjit, Berkane, and Dusart [4] concerning another upper bound for σ(n)/n. Balazard [11, p. 257] showed that for every positive integer N , one has…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the present author [7,Theorem 1.3] proved that the inequality σ(n) n < e γ log 2 n + 0.0094243e γ log 2 2 n holds unconditionally for every integer n > 5040. The initial motivation to write this paper is based on a recent paper by Aoudjit, Berkane, and Dusart [4] concerning another upper bound for σ(n)/n. Balazard [11, p. 257] showed that for every positive integer N , one has…”
Section: Introductionmentioning
confidence: 99%